Gino Arias (1879-1940) Dalla storia delle istituzioni al corporativismo fascista - Ottonelli, Omar (Premio Ricerca «Città di Firenze», 2012)
Gino Arias (1879-1940), Florentine historian and economist of Israeli origin, was in his later years one of the top theorists of Fascist corporatism, which he came to at the end of an as yet widely unstudied intellectual path. After reconstructing his biography, the book investigates Arias's debut as a law historian, his route towards political economics and subsequent subscription to nationalism, paving the way to his involvement in that Fascist regime of which, paradoxically, he was to be both one of the most feared theorists and most illustrious victims, owing to the exile enforced upon him by the race laws. The appendix to the book offers a wealth of new documentation, including an inventory of his archives, the transcription of 130 letters to Achille Loria and his bibliography.